Educating for preserving biodiversity - Méndez Santos , Isidro Eduardo; Guerra Salcedo, Marisela de La Caridad (Transformación, 2024)
The notion of “culture of diversity” 3T is presented in a new dimension. “That of educating for preserving biodiversity” is advanced together with its main challenges. The need of educating the masses for preserving biodiversity is perhaps the most outstanding to be faced, particularly if pedagogic requirements and the diversity of population is to be met. Likewise, it should help to put individuals in contact with the many elements conforming biodiversity and lead them to recognize its value ethically and esthetically. The research presents the framework for designing educating programs enhancing the genetic level, the ecosystem and the qualitative dimension and including materials and energy flood and its meaning for the homeostasis and autopoiesis of the system, together with its interactions with other components for achieving an equilibrium and stability. The importance of the natural evolution tendency is highlighted.